Auditory and cognitive training for cognition in adults with hearing loss: a systematic review and meta-analysis - Lawrence, Blake J.; Jayakody, Dona M. P.; Henshaw, Helen; Ferguson, Melanie A.; Eikelboom, Robert H.; Loftus, Andrea M.; Friedland, Peter L. (Sage, 2018)
This systematic review and meta-analysis examined the efficacy of auditory training and cognitive training to improve cognitive function in adults with hearing loss. A literature search of academic databases (e.g., MEDLINE, Scopus) and gray literature (e.g., OpenGrey) identified relevant articles published up to January 25, 2018. Randomized controlled trials (RCTs) or repeated measures designs were included. Outcome effects were computed as Hedge’s g and pooled using random-effects meta-analysis (PROSPERO: CRD42017076680). Nine studies, five auditory training, and four cognitive training met the inclusion criteria. Following auditory training, the pooled effect was small and statistically significant for both working memory (g = 0.21; 95% CI [0.05, 0.36]) and overall cognition (g = 0.19; 95% CI [0.07, 0.31]). Following cognitive training, the pooled effect for working memory was small and statistically significant (g = 0.34; 95% CI [0.16, 0.53]), and the pooled effect for overall cognition was large and significant (g = 1.03; 95% CI [0.41, 1.66]). However, this was dependent on the classification of training approach. Sensitivity analyses revealed no statistical difference between the effectiveness of auditory and cognitive training for improving cognition upon removal of a study that used a combined auditory–cognitive approach, which showed a very large effect. Overall certainty in the estimation of effect was “low” for auditory training and “very low” for cognitive training. High-quality RCTs are needed to determine which training stimuli will provide optimal conditions to improve cognition in adults with hearing loss.